The incidence of strains of barley yellow dwarf virus in perennial ryegrass crops in southwest and central Scotland - Dempster, L.C.; Holmes, S.J. (Wiley, 1995)
The incidence of barley yellow dwarf virus (BYDV) in perennial ryegrass (Lolium perenne) crops in four areas of south‐west and central Scotland was investigated between March 1988 and February 1989. BYDV was detected in 93·8% of the grass swards using an indirect enzyme‐linked immunosorbent assay (ELISA). This enabled the seasonal periodicity of the BYDV strains to be monitored over 12 months for the first time in Scotland. The incidence of the RPV, PAV and MAV strains of BYDV declined between March and July 1988, before gradually rising in August. Incidence increased markedly in September, especially of the RPV and MAV strains, and then gradually decreased over the winter months, before stabilizing in February 1989. The incidence of the different strains in perennial ryegrass leys varied between geographical areas and between fields within areas. Most ryegrass samples contained a mixture of the three strains of BYDV. RPV was the most common strain in Ayrshire, while the incidence of PAV was highest in Wigtownshire and that of MAV was highest in Dumfriesshire and Stirlingshire. The incidence of BYDV increased with the age of the sward. The role of perennial ryegrass as a source of virus for the infection of cereals is discussed.